Analisis Keselamatan Dan Kesehatan Kerja Dengan Menggunakan Metode Hazop Pada Proses Pan Oil Di PT. X - Moh Jidni Ilman Maarif; Sutrisno Sutrisno (Fakultas Teknik Universitas Tulang Bawang, 2023)
PT. X works in the automotive manufacturing industry. There are various departments in the corporate structure, one of which is K3 (Occupational Health and Safety). This department is an important part of a company. Bearing in mind that all machines and equipment used have potential hazards. Therefore, the purpose of this research is to examine the risk of work accidents that endanger the safety and health of employees. To control the potential for work accidents, the HAZOP method was chosen. The HAZOP approach was used to conduct this research. Hazard and Operability Studies (HAZOP) was founded by ICI, a British chemical company. As a result, HAZOPs are increasingly being used in the chemical sector where they will be used in dealing with accidents that occur due to negligence of workers. The results obtained when conducting research using the hazop method obtained 3 levels of hazard risk and showing the percentage of each level of risk, including 50% low risk, 25% high risk, and 25% extreme risk. Low risk is the process of using manual equipment and forklifts, high level of risk in the machining process, and extreme level of risk in the casting process. Keywords: Accident, hazop, health, safety, work